Stomata on the primary root of Ceratonia siliqua - Christodoulakis, N.S.; Psaras, G.K. (Annals of Botany, 1987)
Anomocytic stomatal complexes observed with light and scanning electron microscopes on the primary roots of Ceratonia siliqua (carob tree) are described. Stomata are randomly distributed throughout the surface of the root zones which possess mature vascular tissues, i.e. from the zone of root hairs to the transition zone. Stomatal orientation does not follow that of the root epidermal cells whilst their distribution does not seem to form a regular pattern. © 1987 Annals of Botany Company.
Keywords: Ceratonia siliqua; Primary root; Stomata